Silk Embolic Material for Catheter‐Directed Endovascular Drug Delivery. Issue 2 (21st November 2021) - Hu, Jingjie; Albadawi, Hassan; Zhang, Zefu; Salomao, Marcela A.; Gunduz, Seyda; Rehman, Suliman; D'Amone, Luciana; Mayer, Joseph L.; Omenetto, Fiorenzo; Oklu, Rahmi
Abstract: Embolization is a catheter‐based minimally invasive procedure that deliberately occludes diseased blood vessels for treatment purposes. A novel silk‐based embolic material (SEM) that is developed and optimized to provide tandem integration of both embolization and the delivery of therapeutics is reported. Natural silk is processed into fibroin proteins of varying lengths and is combined with charged nanoclay particles to allow visibility and injectability using clinical catheters as small as 600 μm in diameter at lengths >100 cm. SEMs loaded with fluorochrome labeled bovine albumin and Nivolumab, which is among the most used immunotherapy drugs worldwide, demonstrate a sustained release profile in vitro over 28 days. In a porcine renal survival model, SEMs with labeled albumin and Nivolumab successfully embolize porcine arteries without recanalization and lead to the delivery of both albumin and Nivolumab into the interstitial space of the renal cortex. Mechanistically, it is shown that tissue delivery is most optimal when the internal elastic membrane of the embolized artery is disrupted. SEM is a potential next‐generation multifunctional embolic agent that can achieve embolization and deliver a wide range of therapeutics to treat vascular diseases including tumors. Abstract : Embolic materials today are clinically approved for achieving vascular occlusion. In this work, a biomaterial comprising silk fibroin and nanoclay is developed and optimized as a multifunctional embolic agent that offers both embolization and drug‐delivery capabilities. The silk embolic material exhibits excellent transcatheter injectability, mechanical strength, biocompatibility, and hemocompatibility to serve as a catheter‐directed embolic drug carrier for the treatment of vascular diseases.